STUDY ON THE METHODOLOGY OF LANGUAGE TEACHING TO INCREASE LANGUAGE AWARENESS OF ESL STUDENTS - Khusanova, Indira (Журнал иностранных языков и лингвистики, 2023)
Our article introduces innovative innovations and techniques, the ability to apply modern teaching methods, which allows you to understand new material faster and easier. By mutually coordinating different methods, the teacher can create his special education program.